Identifikasi Galur Tetua Padi Hibrida dengan Marka SSR Spesifik dan Pemanfaatannya dalam Uji Kemurnian Benih - Mulsanti, Indria W.; Surahman, Memen; Wahyuni, Sri; Utami, Dwinita W. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2013)
DNA finger printing of hybrid rice variety and their parental lines are important molecular traits as a tool in plant variety protection, DUS test, and seed purity assessment. Molecular markers including microsatellite (SSR) markers have been used in varietal assessment. This study was aimed to identify specific SSR markers that can be used to distinguish parent lines of hybrid rice and to assess seed purity. The experiment was conducted in 2011 at Biology Molecular Laboratory of ICABIOGRAD, Bogor. Sixteen SSR markers were used to identify parental lines of five hybrid varieties of rice. Two hybrid varieties (F1), Hipa 6 and Hipa 7, were used in the seed purity assessment. Seven markers were polymorphic, and six of them (RM206, RM263, RM276, RM346, RM335, RM570) were capable of distinguishing parental lines of the five hybrid varieties. RM 346 marker could be used for testing seed purity of Hipa 6, while RM 206 marker for Hipa 7. Specific SSR marker was capable of distinguishing a false hybrid rice that might not be recognized by the grow out test in the field.